2016
DOI: 10.3389/fmicb.2016.01333
|View full text |Cite
|
Sign up to set email alerts
|

New Genomic Insights into “Entotheonella” Symbionts in Theonella swinhoei: Mixotrophy, Anaerobic Adaptation, Resilience, and Interaction

Abstract: “Entotheonella” (phylum “Tectomicrobia”) is a filamentous symbiont that produces almost all known bioactive compounds derived from the Lithistida sponge Theonella swinhoei. In contrast to the comprehensive knowledge of its secondary metabolism, knowledge of its lifestyle, resilience, and interaction with the sponge host and other symbionts remains rudimentary. In this study, we obtained two “Entotheonella” genomes from T. swinhoei from the South China Sea through metagenome binning, and used a RASTtk pipeline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 68 publications
0
23
1
Order By: Relevance
“…Entotheonella strains described here (99.9% average nucleotide identity), and should thus belong to the same candidate species. In contrast to our analysis, Liu et al (52) claim that they identified the CalvinBenson cycle for CO 2 fixation (via ribulose-1,5-bisphosphate carboxylase), candidates for crassulacean acid metabolism (a phenomenon exclusively known in plants), a type VI secretion system, and a complete system for endospore formation. Despite extensive manual and automated reinvestigation of our dataset as well as the sequence data provided for the Chinese sponge, we cannot find any evidence for these genomic features.…”
Section: Resultscontrasting
confidence: 99%
“…Entotheonella strains described here (99.9% average nucleotide identity), and should thus belong to the same candidate species. In contrast to our analysis, Liu et al (52) claim that they identified the CalvinBenson cycle for CO 2 fixation (via ribulose-1,5-bisphosphate carboxylase), candidates for crassulacean acid metabolism (a phenomenon exclusively known in plants), a type VI secretion system, and a complete system for endospore formation. Despite extensive manual and automated reinvestigation of our dataset as well as the sequence data provided for the Chinese sponge, we cannot find any evidence for these genomic features.…”
Section: Resultscontrasting
confidence: 99%
“…Urease genes were also found in other spongeassociated microbial genomes and microbiomes (Hallam et al, 2006;Siegl et al, 2011;Bayer et al, 2014;Liu et al, 2016). Together with the phylogenetic diversity found for ureC genes and transcripts found in the sponge Xestospongia testudinaria (Su et al, 2013), these data indicate that urea degradation is a common trait of sponge-associated microorganisms.…”
Section: Metabolic Features Of Diatoms and The Spongementioning
confidence: 53%
“…CC BY 4.0 License. Fiore et al, 2015;Han et al, 2013;Li et al, 2014;Liu et al, 2016;Liu et al, 2012;Webster and Taylor, 2012;Zhang et al, 2013;Zhuang et al, 2018).…”
Section: Denitrification As a Common Feature Of Cold-water Spongesmentioning
confidence: 99%